(untitled) (Journal of Asian Development Studies, 2026)
Social capital is recognized as a catalyst of economic growth and wellbeing in economic literature. The current study examined the relationship between social capital, proxied by generalized trust, and individuals’ wellbeing in the context of a developing country, specifically Pakistan. Data from the World Values Survey Wave 7 (WVS-7) are used, and an ordered probit model and Average Marginal Effects (AMEs) are employed for estimation. The main contribution and finding of this study is the identification ofa “trust paradox” in Pakistan. The ordered probit model and AME results demonstrate that trusting individuals report lower life satisfaction than distrusting individuals. The study confirms that the probability of trusting individuals being in higher life satisfaction outcomes (10 and 9) is significantly lower than the probability of cautious individuals showing distrust. Based on this empirical analysis, it is concluded that in low-trust environments, trust is not rewarding and may lead to negative outcomes (i.e., lower wellbeing). In addition to the main findings, freedom and control over life, health, and financial satisfaction emerged as important predictors of life satisfaction. Moreover, the analysis of the gender variable showed that, on average, male respondents reported lower life satisfaction than their female counterparts. The study recommends devising policies to reduce the vulnerability of trusting people and ensure a safe social environment where the majority can be trusted, and where trust brings positive outcomes rather than negatively impacting one’s wellbeing.